ChemInform Abstract: A Facile Synthesis of 2‐(2‐Phenyl‐4H‐chromen‐4‐ylidene)‐2H‐indene‐1, 3‐diones and Related Compounds Involving an Interesting Aerial Oxidation. Issue 48 (December 2015) - Guha, Chayan; Samanta, Swati; Sepay, Nayim; Mallik, Asok K.
Abstract: The Amberlyst‐15 catalyzed reaction of 2‐hydroxychalcones with indane‐1, 3‐dione provides the title compounds (III) and (V) via a Michael addition/cyclization/dehydration/oxidation sequence.